SITUATION USING CARBAPENEM (Vietnam Journal of Community Medicine, 2021)
Objective: To survey the use of carbapenem antibiotics at An Sinh General Hospital. Subjects and methods: retrospective descriptive study on 100 medical records of patients being treated in departments of An Sinh General Hospital from June 1st, 2020 to December 31st, 2020. Results: The carbapenem antibiotic used at An Sinh General Hospital mainly indicated for the treatment of pneumonia accounted for the highest percentage with 53.3%. There were 100% of strains of Haemophilus influenzae; Rhizobium radiobacter; Proteus. cp; Streptococcus mitis, which was also sensitive to carbapenem. 100% strains of Stenotrophomonas maltophilia bacteria was resistant to meropenem; 01 strain of Burkhorderia vietnamiensis was isolated against imipenem; 2 of 3 strains of Staphylococcus aereus isolated were resistant to meropenem. Carbapenem was mainly used in combination regimens. The proportion of the combination in the initial regimen was 100%. The rate of combination of 3 antibiotics was 22.7%. In the replaceable regimen, the combination rate was 82.2%. Conclusion: The carbapenem group was indicated for the treatment of pneumonia. Strains of the bacteria Haemophilus influenzae; Rhizobium radiobacter; Proteus. cp; Streptococcus mitis was also sensitive to carbapenem. Bacteria strains Stenotrophomonas maltophilia, Burkhorderia vietnamiensis and Staphylococcus aereus were resistant to meropenem. Carbapenem was mainly used in combination regimens.
Keywords: The situation of usage of antibiotics and Carbapenem antibiotic